The electrochemical behaviour of cobalt in alkaline solutions : Part I. The potentiodynamic response in the potential region of the Co/CoO couple - Gomez Meier, Humberto (1982)
The potentiodynamic response of cobalt in KOH solutions (10−2 M⩽c⩽2.5 M) in the potential range of the thermodynamic stability of the Co(II) species reveals two limiting electrochemical behavirours. One of them corresponds to the first potentiodynamic scan and the other is associated with the stabilized E/I profile resulting after a prolonged potential scanning. The former is related to the large contribution of the metal electrodissolution process. The second is explained in terms of reactions taking place at the sandwich-type structured interface. Ageing effects of Co(II) surface species are also considered in the interpretation of results.